2007
DOI: 10.1007/s10661-007-9678-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heavy metal enrichment factors and the degree of contamination in marine sediments from Tamaki Estuary, Auckland, New Zealand

Abstract: Eight sediment cores recovered from Tamaki Estuary were analysed for Cu, Pb, Zn, and Cd using downward cored sub-samples. The results indicate a significant upward enrichment in heavy metals with the highest concentrations found in the uppermost 0-10 cm layer. Assessment of heavy metal pollution in marine sediments requires knowledge of pre-anthropogenic metal concentrations to act as a reference against which measured values can be compared. Pristine values for the cored sediments were determined from flat "b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
493
1
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,010 publications
(545 citation statements)
references
References 25 publications
(33 reference statements)
1
493
1
15
Order By: Relevance
“…where C n is the measured concentration of the heavy metal in the sediment, constant 1.5 is the background matrix correction factor due to lithogenic effects (Abrahim and Parker 2008;Çevik et al 2009;Qian et al 2005), B n is the geochemical local background levels (LBLs) of Henan Province (EMC 1990) (Table 1), and n is the number of analyzed elements.…”
Section: Evaluation Of Contamination Degree Of Heavy Metalsmentioning
confidence: 99%
See 2 more Smart Citations
“…where C n is the measured concentration of the heavy metal in the sediment, constant 1.5 is the background matrix correction factor due to lithogenic effects (Abrahim and Parker 2008;Çevik et al 2009;Qian et al 2005), B n is the geochemical local background levels (LBLs) of Henan Province (EMC 1990) (Table 1), and n is the number of analyzed elements.…”
Section: Evaluation Of Contamination Degree Of Heavy Metalsmentioning
confidence: 99%
“…Toxicity weight 1 was assigned for Cr, Zn, and Mn; 2 was assigned for Cu, 5 for Pb, and 300 for Cd (Singh et al 2002). The contamination levels may be classified descriptively for increasing I geo (Forstner et al 1993) and mC d (Abrahim and Parker 2008) values, and the sediment classification is given for the SPI values (Singh et al 2002) listed in Table 2. When PLI index is more than 1, it means that metal pollution exists; otherwise, there is no pollution (Varol 2011).…”
Section: Evaluation Of Contamination Degree Of Heavy Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of these conflicting features, selecting an appropriate background value is essential for obtaining reliable EFs. Other research has also shown that EF values will change considerably with different baseline values (Abrahim and Parker 2008;Celis-Hernandez et al 2013). Consequently, it is more logical and appropriate to use the UCCEC for normalization than to use regional background values or the UCW.…”
Section: Enrichment Factormentioning
confidence: 99%
“…Various hydrological processes and sediment physicochemical properties significantly influence the biochemical processes of heavy metals in marshes. There has been intensely increasing interest in understanding the pollution of heavy metals in coastal marsh due to the great influences of human activities (Li et al 2000(Li et al , 2007Caeiro et al 2005;Abrahim and Parker 2008;Bai et al 2011Bai et al , 2012Xiao et al 2013). Exploring heavy metal accumulation in plants for the remediation (or phytoremediation) of coastal environment is of great significance (Chaney et al 1997;Deng et al 2004).…”
Section: Introductionmentioning
confidence: 99%